The Role of Environmental Management and Green Innovation (case study of BUMDES (Village Business Agency)) - Gustin, Fajri Aniva; Nur, Sofyan Ashari; Yuniawan, Ryan (Universitas Muhammadiyah Surakarta, 2019)
Purpose: Environmental Based Management is a discussion that is being carried out, on the other hand Indonesia has a business entity that greatly contributes to the welfare of the people and has a good environmental-based management namely BUMDES (Village-Owned Enterprises). This study aims to analyze the relationship between environmental management and green innovation on firm performance for BUMDES.Methodology: This study uses a quantitative method with PLS (Partial Least Square). Data was collected by questionnaire distribution of 110 respondents from BUMDES managers.Results: The results of this study indicate that environmental management and green innovation have a positive and significant effect on firm performance.Applications/Originality/Value: This research is important because of the limited literature that discusses environmental management and green innovation at Village Business Agency such as BUMDES. The results of this study are expected to help the government and managers of BUMDES to further develop environmental management and green innovation so as to improve the performance of BUMDES.